Peran Notaris Pembuatan Akta Fidusia sebagai Perlindungan Konsumen Berdasarkan UU Nomor 8 Tahun 1999 (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study discusses the role of notaries in making fiduciary deeds for consumer protection based on the Law of the Republic of Indonesia Number 8 of 1999. The purpose of this study is to determine how the role of notaries in making fiduciary deeds for consumer protection and what obstacles occur in the process of making fiduciary deeds. , in the event of a dispute, how can it be resolved based on Law of the Republic of Indonesia Number 8 of 1999. The approach method used is the normative juridical method. The research specification used in this research is descriptive analytical. The sources and types of data in this study are secondary data. These problems are studied with the theory of legal certainty and legal protection. Based on the results of the research, the role of the notary in providing services to the public, especially for making fiduciary deeds, is things that must be done so that no parties are harmed and the deed can provide protection and legal certainty. The parties come face to face with the Notary. Based on the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, making a Notary Deed, must be before a Notary according to the form and procedure stipulated by the Law, and refuse to make a deed, if power of attorney that is contrary to Article 18 paragraph (1) letter h. Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection, which states that the power of attorney is an integral part of the standard agreement prepared by the fiduciary recipient, and Law No. 8 of 1999 divides consumer dispute resolution into 2 (two) parts, namely: Settlement of disputes outside of court and Settlement of consumer disputes through courts (litigation).